Relationship of Knowledge and Attitude about Stunting with Stunting Evidence - Farihah Indriani; Romdiyah; Fibrinika Tuta Setiani (Babali Nursing Research, 2022)
Introduction: Stunting is an abnormal growth of children that occurs in toddlers due to lack of nutrition from the womb until birth. Children who experience stunting have impaired growth and development. The objectives of the study was to measure the relationship between knowledge and attitudes about stunting with the incidence of stunting. Methods: The research approach used a descriptive study with a cross sectional design. The respondents in this study were all mothers that had toddlers. The sample of the study were mothers who had children aged 0–59 months as many as 48 mothers. Analysis of univariate with frequency distribution and bivariate analysis with Chi-Square. Results: Based on the results of the research, knowledge about stunting was good, namely 37 (77.1%), and mother's attitude about stunting was positive at 40 (83.3%) and stunting incidence was 62.5%. The findings with the Chi-Square test analysis revealed a significant effect between knowledge, attitudes about stunting and the incidence of stunting where knowledge with prevalence values and confidence intervals is 7.2 (1.59 – 32, 67) and attitudes with prevalence values and confidence intervals of 7, 0 (1.23 – 39.78). Conclusion: The study declares that mothers with good knowledge effect signifantly toward incidence of stunting. Mothers with positive attitudes effect significantly toward stunting incidences.